Healthy Canadian Mining Communities: Company-Community Partnership for Planning and Development - Rowena Anderson (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
Mining companies are now looking for more effective ways to engage the community in public participation. Consensus-based approaches are becoming the most popularly applied way of achieving meaningful public participation. This paper introduces the principles surrounding consensus-building approaches and the processes for getting them started. The Healthy Communities Movement is one such consensus-based approach that offers a well-established holistic model for conceptualizing a healthy sustainable community. It also highlights the importance of public participation as an essential component of achieving a sustainable community. The paper concludes by illustrating how current company-community relations programs can utilize these models.